The Influence of Country of Origin and Perceived Quality on Consumer Purchase Intentions of Wuling Brand Cars (Case Study on the People of Bengkulu City) - Nugraha, Daffa; Nengsih, Mimi Kurnia (Proceedings Series on Social Sciences & Humanities, 2025)
Consumer purchase intention towards a product is influenced by various factors, including country of origin and perceived quality. This study aims to analyze the effect of country of origin and perceived quality on the purchase intention of Wuling cars in Bengkulu City. A quantitative research method with a survey approach was employed in this study. The research population includes all residents of Ratu Agung District, Bengkulu City, with a total sample of 105 respondents. Data were collected through a questionnaire and analyzed using multiple linear regression. The results show that country of origin has a positive and significant effect on purchase intention, indicating that public perception of Wuling’s country of origin influences their level of interest in the brand. Additionally, perceived quality also has a positive and significant effect on purchase intention, meaning that the higher the perceived quality of Wuling cars, the greater the public interest in purchasing them. This study confirms that country of origin and perceived quality are crucial factors influencing consumer purchase intention. Therefore, marketing strategies that enhance the positive image of the country of origin and improve product quality perception should be continuously optimized to strengthen Wuling’s competitiveness in the Indonesian market, particularly in Bengkulu City.